2011
DOI: 10.1016/j.childyouth.2010.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Are social networking sites a source of online harassment for teens? Evidence from survey data

Abstract: Media reports on incidences of abuse on the internet, particularly amongst teenagers, are growing at an alarming rate causing much concern among parents of teenagers and legislations aimed at regulating internet use among teenagers. Past studies have found that one in five youth were exposed to sexual solicitation, one in seventeen were harassed or threatened and only a fraction reported these cases while more than 63% reported being upset, embarrassed or stressed as a result of these unwanted contacts. Social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(49 citation statements)
references
References 6 publications
2
40
0
7
Order By: Relevance
“…Certainly within the current sample all respondents had had sexual relationships with adults, although many of them described these relationships as being unsatisfactory. What was also of note was that these men described themselves often seeking young people because of certain information available in their profile, including images, similar to the findings of Sengupta and Chaudhuri (2011) and Malesky (2007). Such information was used to both fuel fantasies, facilitate contact with young people and to accrue a body of information that enabled the skilful manipulation of technological platforms in the absence of historical expertise.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Certainly within the current sample all respondents had had sexual relationships with adults, although many of them described these relationships as being unsatisfactory. What was also of note was that these men described themselves often seeking young people because of certain information available in their profile, including images, similar to the findings of Sengupta and Chaudhuri (2011) and Malesky (2007). Such information was used to both fuel fantasies, facilitate contact with young people and to accrue a body of information that enabled the skilful manipulation of technological platforms in the absence of historical expertise.…”
Section: Discussionmentioning
confidence: 91%
“…Affordance in the sense used here refers to the quality of an environment (in this case that provided by both the physical and software platform) that enables, facilitates or makes possible an action (Gibson, 1979). For example, there is concern that the use of social networking sites (SNS) in particular may be associated with increasing risk of harm (Staksrud et al, 2012) and with children placing themselves at risk (Sengupta & Chaudhuri, 2011;Noll, Shenk, Barnes, & Putnam, 2009). From an offender perspective, Mitchell, Finkelhor, Jones & Wolak's (2010) survey of law enforcement indicated that SNSs were used to initiate sexual relationships, to provide a means of communication between victim and offender, to access information about the victim, to disseminate information or pictures about the victim, and to get in touch with the victim's friends; SNS's might be said to 'afford' opportunities for offending.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, increased rates of reporting have also been observed amongst adolescents and young adults (Annenberg Public Policy Centre, 2010;Sengupta & Chaudhuri, 2011). In 6 contrast, studies offering demographics of troublemakers have indicated that males are marginally more likely to cause problems online than females (Aricak et al, 2008), especially during the transition from adolescence to adulthood (Annenberg Public Policy Centre, 2010).…”
Section: Online Vulnerability On 'Friend'-based Networkmentioning
confidence: 99%
“…Various studies yielded a number of results in this regard which can be summarized in the way that kids with online activity and specifically with social networking practice are prone to greater online risk and abuse than those who do not. The overall impression of these studies have established the social networking sites to be a definite avoidable one for the children and teens [8,15]. In social networking websites, people create and share personal information that exceeds far above the line of official resume level information.…”
Section: Related Studiesmentioning
confidence: 99%
“…Besides, the online safety for individuals is a major concern as people develop their on-line profile as well as their ongoing activities in the social networking sites [1,8,9,14]. As stated earlier, the social networking platforms are being used for diversified reasons.…”
Section: Introductionmentioning
confidence: 99%